Prevalence and Possibly Related Factors of Stress in Registered Nurse in a Psychiatric Hospital in Northeastern Thailand - Prechaporn, Wisarud; Radchai, Chutithep; Bannakit, Paramin; Sermsri, Pongsathorn; Prasertwit, Patcharanya; Ingsuk, Tanayu; Ditsataporncharoen, Thanapat; Srisaenpang, Sompong (Srinagarind Medical Journal, 2018)
Background and Objectives: Registered nurses in psychiatric hospital are prone to be stressed by work. It could be shown by their work’s habits and responsibilities. Moreover, there is a rise in the number of psychiatric patients over recent years. Therefore, researchers had an objective to study the prevalence of stress in registered nurses in a psychiatric hospital and relating factors. Methods: A descriptive study was conducted in 117 registered nurses in one of the psychiatric hospitals in Northeastern Thailand. A self-administered questionnairewas applied from SPST-20 questionare and modified by literature review and expert opinions. The data was analyzed bySPSS version 17.0 with descriptive statistic and inferential statistic including Pearson’s Chi-square, odd ratio and 95% confidence interval. Results: The overall response rate was 66.7% (78/117). 61.5% of sample size had stress with 95% conferential interval ( 49.80, 72.13 ), 60.5% of this group with height stress. The possibly related factors of stress in this study including the specific factors of registered nurses in a psychiatric hospital, the work-related factors, the work environmental factors, the organization factor, and the individual relationship factor were not statistically significant with the p-values of 0.477 , 0.381 , 0.590 , 0.417 and 0.947, respectively Conclusion: 61.5% of registered nurses in a psychiatric hospital in Northeastern Thailand has stress, hour ever, the factors that we found were not statistically significant